Intervensi Prinsip Responsibility To Protect Terhadap Masyarakat Sipil dalam Situasi Perang Israel – Palestina Tahun 2023 - Zian Azmi Falevi, Renzi; Astuti, Mirsa (Dinasti Review Publisher, 2024)
One of the longest and most complex conflicts in the world is the Israeli-Palestinian conflict. The security situation in the region remains extremely fragile despite peace efforts. In 2023, another escalation of violence occurred, killing civilians. The principle of the responsibility to protect (R2P) is important to discuss in this situation. This study uses normative legal scholarship-also known as positive legal scholarship, doctrinal, or purely as a methodology-to conduct this research. The main focus of the research is written law and legal traditions held by the community. Primary, secondary and tertiary legal materials are included in the secondary data sources, which are an essential component of this methodology.In 2005, the United Nations (UN) established the global Responsibility to Protect (R2P) standard. This concept says that states have the primary responsibility to prevent genocide, ethnic cleansing, crimes against humanity and other human rights violations. This concept is based on existing international rules, such as Articles 1 and 2 of the UN Charter. Violations of R2P principles in the 2023 Israeli-Palestinian conflict have significant legal, security and moral consequences. Such violations are considered war crimes and crimes against humanity for which international tribunals are legally accountable. Security-wise, a prolonged conflict could lead to significant regional instability and refugees. Morally, these violations constitute a human tragedy.